Soft Skills Enhance Employee Contextual Performance: The Case of the Maritime Industry - Maria Chala, Fratzeska; Bouranta, Nancy (KnE Social Sciences, 2021)
The maritime industry holds a prominent position in international business and world trade. This competitive and rapidly growing sector requires a highly trained workforce with specific soft skills, such as the abilities and traits that pertain to personality, attitude, and behavior. Soft skills combined with hard skills influence employees’ ability to work effectively by enhancing their performance. This study focused on the maritime industry and empirically examined the effect of four soft skills (adaptability, communication, problem-solving, teamwork) on employee contextual performance. It also explored whether there is a significant relationship between soft skills and income. An empirical survey was carried out through a self-assessment questionnaire which was administered to managers and employees of Greek shipping companies resulting in 191 usable questionnaires. Exploratory factor analysis, correlation, regression analysis and analysis of variance (ANOVA) were applied to examine the data. It was found that teamwork, problem-solving, adaptability and communication positively affect employee contextual performance. In addition, it was confirmed that problem-solving skills are related to employee income. This study contributes to the literature, defining which soft skills are significant factors in employee contextual performance and income. There is little literature exploring these relationships, and even fewer studies have focused on the maritime industry. This paper highlights the importance of employees developing transferable soft skills to perform effectively in the workplace. Keywords: maritime industry, soft skills, employee contextual performance, income